Cross-CRP Analysis of Capacity Development in the 2017-2022 CRP2 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
This brief provides a summary analysis of the sections of the CGIAR Research Program Portfolio (CRP2) proposals related to capacity development (CD) and assesses whether the ten elements of the Capacity Development Framework 1 were reflected in the proposals and whether the CD outputs and outcomes were reflected in the Theories of Change and Impact Pathways.